CONCEPTUAL UNDERSTANDING OF AMLAPITTA (GASTRITIS) - Wilson, *Nicy; MJ, Prashasth; Dr, Muralidhara (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda has given utmost importance to optimal dietary regimen and its variation as per the season, Agni, Prakruti. When these are not followed, leads to imbalance in Doshas in turn leading to the manifestation of disease. Other contributing factors for the change in food habits are frequent traveling and change of environment which in turn has an effect on an individuals health. So it can be clearly understood that imbalanced food habits are considered as the prime cause of the manifestation of disease in an individual. Amlapitta is such a clinical entity manifesting in the Annavaha Srotas. Amlapitta can be correlated with Acid Peptic Disorders which comprises of Gastro-Oesophageal Reflux Disease, Gastritis, Functional Dyspepsia described in modern science. According to several authors of contemporary science states that, the combination of physiological, environmental, genetic and psychological factors definitely occupy a prime role in the manifestation of the disease. Through this article an attempt is made to compare and understand the Nidana, Samprapti, Purvarupa, Rupa mentioned by various Acharyas and also to analyse through the current lifestyle modifications contributing to the manifestation of the disease Amlapitta.